Theoretical and experimental comparison of gear systems: planetary mechanical transmission and coaxial magnetic gear - Kołodziej, Janusz; Rafał Gabor; Kowol, Marcin; Łukaniszyn, Marian (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
Gear systems in today’s industry are one of the critical pillars providing power transformation and matching speed and torque to application requirements. Reliability, high efficiency, and low operating costs are desirable due to the prevalence of gearboxes. This paper provides a comparative analysis of selected mechanical and magnetic gears, using a specific example to point out the advantages and disadvantages of contactless power conversion. After determining the essence of the operation of the magnetic gear on the base model, two magnetic gear optimization cases are presented, testifying to the application potential. An analysis of the stress distribution in the area of the teeth of the mechanical gearbox and the most stressed element of the magnetic gear – the modulator, was carried out. The effects of temperature and load on losses were measured and simulated, and ultimately, the efficiency characteristics of the two gears were also compared.